An interactive approach towards the development of portable laser cutting machine. (2020) - Vijayakumar, R.; Ramesh, C.; Ezhilarasan, T.; Praveenkumar, P.; Ram Mohan, R.
Abstract: Laser cutter is a technology that uses a laser for cutting, boring and engraving the materials. The accuracy of laser cutter technology is high compared to other traditional technology. It is used in industrial manufacturing applications and also commercials purpose. Laser cutter works by directing the laser through optics and controlled by the control system by following a G-code of the pattern to be cut onto the material. In this project, a 20w laser, low weighted parts and simple mechanism is implemented to make a portable laser cutter. Also, a separate power controller is provided for laser and the stepper motors. Hence, accuracy is obtained by adjusting the power supply of laser. By using the LIGHT BURN software, the G-CODE is generated to navigate the laser head. The images and impression designs are imported to the software to generate the G-CODE and navigate the laser head. In this software, output power of the laser is also controlled. The materials like wood, fibers can be cut efficient in 20w laser.